AWS Certified Cloud Practitioner Study Guide With 500 Practice Test Questions foundational (CLF-C02) exam - Piper, Ben; Clinton, David (Ascent Audio, 2024)
In the newly revised second edition of AWS Certified Cloud Practitioner Study Guide: Foundational (CLF-C02) Exam, a team of veteran IT professionals and educators delivers an up-to-date and easy-to-follow introduction to Amazon's industry-leading cloud technology and the introductory certification exam that demonstrates your understanding of it. Used by thousands of companies across the globe, Amazon Web Services (AWS) is an integral part of business IT operations at firms in virtually every industry and sector. In this book, you'll prepare to pass the recently updated AWS Certification Exam and prove your knowledge of critical AWS cloud technologies and capabilities. You'll find complete and thorough coverage of every topic included on the exam, from infrastructure to architecture and cybersecurity. You'll also discover comprehensive discussions of the AWS Cloud value proposition, as well as billing, account management, and pricing models. The AWS Certified AWS Certified Cloud Practitioner Study Guide is an essential resource for any IT professional that works directly with Amazon Web Services, as well as students in IT fields, and non-technical professionals who work with and alongside technical experts.